Expression and replication of virus-like circular DNA in human cells - Eilebrecht, Sebastian (Sci Rep, 2018)
The consumption of bovine milk and meat is considered a risk factor for colon- and breast cancer formation, and milk consumption has also been implicated in an increased risk for developing Multiple Sclerosis (MS). A number of highly related virus-like DNAs have been recently isolated from bovine milk and sera and from a brain sample of a MS patient. As a genetic activity of these Acinetobacter-related bovine milk and meat factors (BMMFs) is unknown in eukaryotes, we analyzed their expression and replication potential in human HEK293TT cells. While all analyzed BMMFs show transcriptional activity, the MS brain isolate MSBI1.176, sharing homology with a transmissible spongiform encephalopathy-associated DNA molecule, is transcribed at highest levels. We show expression of a replication-associated protein (Rep), which is highly conserved among all BMMFs, and serological tests indicate a human anti-Rep immune response. While the cow milk isolate CMI1.252 is replication-competent in HEK293TT cells, replication of MSBI1.176 is complemented by CMI1.252, pointing at an interplay during the establishment of persistence in human cells. Transcriptome profiling upon BMMF expression identified host cellular gene expression changes related to cell cycle progression and cell viability control, indicating potential pathways for a pathogenic involvement of BMMFs.